Identification and Characterization of Sebaceous Gland Atrophy-Sparing DGAT1 Inhibitors - Muise, Eric S.; Zhu, Yonghua; Verras, Andreas; Karanam, Bindhu V.; Gorski, Judith; Weingarth, Drew; Lin, Hua V.; Hwa, Joyce; Thompson, John R.; Hu, Guanghui; Liu, Jian; He, Shuwen; et al. (PloS one, 2014)
Inhibition of Diacylglycerol O-acyltransferase 1 (DGAT1) has been a mechanism of interest for metabolic disorders. DGAT1 inhibition has been shown to be a key regulator in an array of metabolic pathways; however, based on the DGAT1 KO mouse phenotype the anticipation is that pharmacological inhibition of DGAT1 could potentially lead to skin related adverse effects. One of the aims in developing small molecule DGAT1 inhibitors that target key metabolic tissues is to avoid activity on skin-localized DGAT1 enzyme. In this report we describe a modeling-based approach to identify molecules with physical properties leading to differential exposure distribution. In addition, we demonstrate histological and RNA based biomarker approaches that can detect sebaceous gland atrophy pre-clinically that could be used as potential biomarkers in a clinical setting.